The treasury of David ; v. 7 a commentary on the Psalms in seven volumes - Spurgeon, Charles Haddon, 1834-1892 (London, UK Hodder and Stoughton, 1905)
Includes bibliographical references and index. Contents : v. 7 : Psalms 125-150.
Keywords: Bible. O.T. Psalms CXXV-CL -- commentaries